Treadmill Training Increases SIRT-1 and PGC-1α Protein Levels and AMPK Phosphorylation in Quadriceps of Middle-Aged Rats in an Intensity-Dependent Manner. (7th June 2014) - Oliveira, Nara R. C.; Marques, Scherolin O.; Luciano, Thais F.; Pauli, José R.; Moura, Leandro P.; Caperuto, Erico; Pieri, Bruno L. S.; Engelmann, Julia; Scaini, Gisele; Streck, Emilio L.; Lira, Fabio S.; Pinho, Ricardo A.; et al.
Abstract : The present study investigated the effects of running at 0.8 or 1.2 km/h on inflammatory proteins (i.e., protein levels of TNF- α, IL-1 β, and NF- κ B) and metabolic proteins (i.e., protein levels of SIRT-1 and PGC-1 α, and AMPK phosphorylation) in quadriceps of rats. Male Wistar rats at 3 (young) and 18 months (middle-aged rats) of age were divided into nonexercised (NE) and exercised at 0.8 or 1.2 km/h. The rats were trained on treadmill, 50 min per day, 5 days per week, during 8 weeks. Forty-eight hours after the last training session, muscles were removed, homogenized, and analyzed using biochemical and western blot techniques. Our results showed that: (a) running at 0.8 km/h decreased the inflammatory proteins and increased the metabolic proteins compared with NE rats; (b) these responses were lower for the inflammatory proteins and higher for the metabolic proteins in young rats compared with middle-aged rats; (c) running at 1.2 km/h decreased the inflammatory proteins and increased the metabolic proteins compared with 0.8 km/h; (d) these responses were similar between young and middle-aged rats when trained at 1.2 km. In summary, the age-related increases in inflammatory proteins, and the age-related declines in metabolic proteins can be reversed and largely improved by treadmill training.